PERAN KEPEMIMPINAN PADA KEBERHASILAN PERUSAHAAN KELUARGA - Sentot Imam Wahjono (UMSurabaya Publishing, 2008)
Family business has its own characteristics. There are three other factors that influence the successful of family firms, namely: ownership, business, and family. Because of the three factors that influence each other here, which surfaced in the value of family firms is harmony. Yet family firms still have to achieve the goal of profit and growth. That's why leadership is necessary. In family firms, especially those that are still dominated by the role of founders and their families need leadership that can be flexible to adjust the leadership style of the owner or owners of a family with subordinates or employees. Leadership models that match the characteristics of family firms, such as situational leadership style that is based on the theory of Hersey-BlanchardKey words: situational leadership, leadership effectiveness, satisfaction leadership,entrepreneurship